2010
DOI: 10.1177/147470491000800209
|View full text |Cite
|
Sign up to set email alerts
|

The Attention-Getting Capacity of Whines and Child-Directed Speech

Abstract: The current study tested the ability of whines and child-directed speech to attract the attention of listeners involved in a story repetition task. Twenty non-parents and 17 parents were presented with two dull stories, each playing to a separate ear, and asked to repeat one of the stories verbatim. The story that participants were instructed to ignore was interrupted occasionally with the reader whining and using child-directed speech. While repeating the passage, participants were monitored for Galvanic skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Younger siblings’ effective use of reward power, specifically negative behavior (i.e., whining, crying) in influencing their parent(s) and/or older sibling may reflect the younger's less sophisticated cognitive skills (Kuczynski & Parkin, ; Rinaldi & Howe, ). Furthermore, the history of family interactions perhaps influenced the parents’ view of the younger as a victim (Persram et al., ), who in turn may have developed a relational schema for using negative reinforcement to achieve his or her goal (Chang & Thompson, ; Martin & Ross, ). Given this, Kramer () recommends parents respond to their younger child so as to enhance more sophisticated and emotionally positive power strategies when interacting with others.…”
Section: Discussionmentioning
confidence: 99%
“…Younger siblings’ effective use of reward power, specifically negative behavior (i.e., whining, crying) in influencing their parent(s) and/or older sibling may reflect the younger's less sophisticated cognitive skills (Kuczynski & Parkin, ; Rinaldi & Howe, ). Furthermore, the history of family interactions perhaps influenced the parents’ view of the younger as a victim (Persram et al., ), who in turn may have developed a relational schema for using negative reinforcement to achieve his or her goal (Chang & Thompson, ; Martin & Ross, ). Given this, Kramer () recommends parents respond to their younger child so as to enhance more sophisticated and emotionally positive power strategies when interacting with others.…”
Section: Discussionmentioning
confidence: 99%
“…A receiver‐psychology perspective may be particularly illuminating in arenas that involve conflicts of interest. Whining by children has been shown to capture increased attention from listeners and cause physiological arousal in both parents and nonparents, which may have implications in modern contexts where nonrelatives are often responsible for much of infant care. Infant crying may be an honest signal of vigor or need, but it also has the potential to exploit parents and others into exceeding levels of investment that are optimal for themselves .…”
Section: Discussionmentioning
confidence: 99%
“…Sears et al (2014) found that whining followed the refusal of a request, and failure to attain a desired outcome. Chang and Thompson (2010) also suggest whining occurs in the context of unmet goals. Taking a more interactionally grounded approach, Schegloff (2005) notes the use of whining intonation in the actions of imploring and entreating, and suggests that children can be said "not 'to whine,' but to 'do whining'" (p. 469).…”
Section: Introductionmentioning
confidence: 96%
“…Defined as "a low somewhat shrill protracted cry" (Oxford English Dictionary), the distinctive intonational pattern of whining involves exaggerated rising pitch contours, increased loudness, and slower production (Sokol, et al, 2005). While this makes whining a useful attention-getting practice, whining has been found to be more annoying and distracting than other speech forms (Chang & Thompson, 2010). A second problem with whining is that it is generally considered to involve heightened negative affect, typically to "represent discontent" (Chang & Thompson, 2010, p. 261).…”
Section: Introductionmentioning
confidence: 99%